Toward next-generation primate neuroscience: a collaboration-based strategic plan for integrative neuroimaging - Milham, M; Petkov, C; Belin, P; Mars, R; Howard, A; Mitchell, A (Cell Press, 2021)
Open science initiatives are creating opportunities to increase research coordination and impact in nonhuman primate (NHP) imaging. The PRIMatE Data and Resource Exchange community recently developed a collaboration-based strategic plan to advance NHP imaging as an integrative approach for multiscale neuroscience.